Disability Self-evaluation for Low Back Pain in COVID-19 Pandemic - Listya Tresnanti Mirtha; Diandra Amandita Priambodo; Dinda Nisrina; Evita Stephanie; Kharisma Zatalini Giyani (Indonesian Journal of Physical Medicine & Rehabilitation, 2021)
ABSTRACTIntroduction: Low back pain (LBP) interferes with daily activities, which is why monitoring offunctional disability is important. Non-urgent hospital visits are reduced due to the COVID-19 pandemic.Functional disability questionnaires serve as an alternative fo r patients to self-monitor their condition.Methods: This case-based study aimed to compare the Quebec Back Pain Disability Scale (QBPDS) withthe Oswestry Disability Index (ODI) on their responsiveness in assessing functional disability of patientswith LBP. Four databases (PubMed, Scopus, Cochrane, and Embase) were searched for literature. Twoeligible studies were included in this report. The studies were assessed using the Centre for Evidence-Based Medicine critical appraisal tool for diagnostic studies. Data collected on the responsiveness ofODI and QBPDS were measured using the area under the curve (AUC) of a receiver operating curve(ROC), sensitivity, and specificity.Result: Both studies reported higher AUC values for ODI than QBPDS. One study reported highersensitivity in ODI and identical specificity values for both ODI and QBPDS. QBPDS has comparableresponsiveness to ODI in assessing functional disability of pat ients with LBP.Conclusion: Therefore, patients with low back pain can self-monitor their condition with QPBDS, as itis comparable to ODI and suitable for self-monitor during the C OVID-19 pandemicKeywords: assessment, disability evaluation, low back pain, musculoskeletal pain, surveys andquestionnaires